Clinton cash the untold story of how and why foreign governments and businesses helped make Bill and Hillary rich - Schweizer, Peter (Harper Collins, 2015)
In 2000, Bill and Hillary Clinton owed millions of dollars in legal debt. Since then, they've earned over
Keywords: Clinton, Bill, 1946---Finance, Personal